Analisis Persepsi Masyarakat Terhadap Pengelolaan Ekosistem Mangrov di Kawasan Mangrov Biringkassi Kabupaten Pangkep - Mappasomba, Zulkifli; Haidir, Muh (Universitas Tanjungpura, 2024)
This study aims to analyze public perception of mangrove management in the Biringkassi mangrove area of Pangkep regency. This research is important because the surrounding community does not get more education and attention from the government. This research is a descriptive research with a qualitative approach. Researchers conducted in-depth interviews with 45 purposively selected respondents using thematic category content analysis techniques to identify themes or patterns in the interview. The result: The level of understanding and knowledge of the community is low. Community participation is in the moderate category even though it is known that public perception of the benefits of mangrove ecosystems for them is quite good. Therefore, citizen involvement in maintaining mangrove ecosystems that are still at the middle level needs to be increased, and implementing programs such as: (1) increasing public awareness of the importance of mangrove ecosystems, (2) educating the public about mangrove ecosystem management, (3) intensifying government policies on planting and conservation, and (4) establishing effective communication between the government and the community